Development of a Mobile Functional Near-infrared Spectroscopy Prototype and its Initial Evaluation: Lessons Learned - Volkening, Nils; Unni, Anirudh; Becker, Sabeth; Rieger, Jochem W; Fudickar, Sebastian; Hein, Andreas (Proceedings of the 11th PErvasive Technologies Related to Assistive Environments Conference on - PETRA '18, 2018)
This paper presents a new mobile near-infrared functional spectroscopy (fNIRS) device, with digital detectors that can be placed anywhere on the head and fit into standard caps to measure cortical brain activation. The device's functionality was evaluated in two steps, i.e. first, by means of simple pulse measurements and second, in a motor cortex study with nine subjects. In this study, the subjects had to alternate between right and left hands while using hand-held strength trainers. While the signals from the mobile prototype were not yet stable enough across all channels to perform analysis such as statistical parametric mapping, it was able to measure significant brain activation changes over the area of the motor cortex with the mobile prototype when the contralateral hand was activated in four subjects. In contrast, the device was yet unable to measure ipsilateral activities. The problems encountered and possible methods to improve signal acquisition are discussed at the end of the paper.
Keywords: accepted; AMTCSE; AMTUNI; fnirs; full paper; functional near-infrared spectroscopy; is a non-invasive; method for the imaging; mobile fnirs; motor cortical activity; of the central nervous; prototype; system and is used